BacPROTAC approach for tuberculosis drug discovery - Bonjorno, Andressa Francielli [UNESP]; Pavan, Aline Renata; Lopes, Juliana Romano [UNESP]; Prates, João Lucas Bruno [UNESP]; de Souza, Mateus Mello [UNESP]; Scarim, Cauê Benito [UNESP]; dos Santos, Jean Leandro [UNESP] (Elsevier, 2024)
According to the World Health Organization, tuberculosis (TB) continued to be a significant health burden in 2023, affecting an estimated 10 million individuals and resulting in 1.3 million deaths globally. One of the greatest challenges in combating TB is the rise of Multi-Drug Resistant (MDR) strains, which complicate and diminish the effectiveness of treatment. The PROteolysis Targeting Chimeras (PROTAC) strategy has emerged as a promising alternative in the quest for anti-Mycobacterium tuberculosis (Mtb) agents. The application of PROTACs in addressing MDR-TB represents an innovative and potentially effective approach, opening new avenues for the discovery of therapeutic agents against this disease. In this chapter, we discussed the challenges encountered in developing compounds to combat TB, particularly MDR-TB. Additionally, we explored the mechanisms underpinning this novel strategy and present the most recent advancements in this field.